Analisis Kontribusi Parkir Elektronik (E-Parkir) Dalam Meningkatkan Pendapatan Asli Daerah Kota Medan Dengan Pendekatan Triple Helix - Fandy Rangkuty, Muhammad Hafif; Nawawi, Zuhrinal M.; Nasution, Juliana (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Parking tax is one of the regional revenues that contributes to increasing local revenue (PAD), so it is hoped that the parking tax can be used as an alternative to government funding to support increasing regional potential. The purpose of this study was to find out how the parking tax collection system at the Medan City Regional Tax and Retribution Management Agency, and the level of realization of parking tax collection on Regional Revenue at the Medan City Regional Tax and Retribution Management Agency, also to find out the obstacles and efforts made by the Management Agency Medan City Regional Taxes and Levies to optimize Parking tax revenue. The research method used in the preparation of this final assignment is a qualitative descriptive method. The type of data used in this research is quantitative data, namely research obtained directly from the company, including parking retribution receipts and parking tax data. This research tries to apply the e-parking policy communication carried out by the Medan City Government using the triple helix model. From this model approach, e-parking is seen from several important elements involved in the policy. Starting from the Medan City Government represented by the Medan City Transportation Service and PT Logika Garis Elektronik (LGE) as the e-parking manager, and academics as the wider community who are e-parking users and provide academic views. As well as business people as entrepreneurs who are around the road that implement e-parking. By using a qualitative-descriptive method, this study shows that this e-parking program comes with various pros and cons and looks at how two official institutions, in this case the City Government and PT LGE, carry out the process of communicating policies to the public, especially to parking attendants and public.